PENDAMPINGAN PEMASARAN SYARIAH USAHA KECIL GULA AREN DI DESA PALAK SIRING KECAMATAN KEDURANG KEBUPATEN BENGKULU SELATAN - Rahayu, Levia; Hak, Nurul; Hasibuan, Rahmat Putra Ahmad (JURNAL ILMIAH EDUNOMIKA, 2024)
The final assignment with the title "Shariah Assistance for Palm Sugar Small Businesses in Palak Siring Village, Kedurang District, South Bengkulu Regency" was prepared by Levia Rahayu, student of the Sharia Economics Study Program. With assistance in the form of Marketing techniques with Social Media Marketing, and Product Packaging Optimization, especially palm sugar entrepreneurs. Due to the low level of knowledge and skills regarding marketing and packaging optimization among palm sugar entrepreneurs in Palak Siring Village, Kedurang District, South Bengkulu Regency, the parties involved are the village head, palm sugar entrepreneurs, and the palm sugar marketing community in Palak Siring Village, Kedurang District, South Bengkulu Regency. .This assistance is carried out for 5 months, starting from October 13 2023- March 15 2024. With a total cost of Rp. 810,000. It is hoped that future researchers who wish to continue community service on the same object can carry out more educational activities related to sharia marketing.